The Correlation between Human Capital and Morality and Its Effect on Economic Performance : Theory and Evidence - Balan, David J.; Knack, Stephen (2012)
This paper incorporates morality -- defined as lower utility from consuming goods obtained through appropriative rather than productive activities -- into a simple static general equilibrium model in which agents choose whether to be producers or appropriators. The authors analyze the relationship between the correlation between morality and human capital on the one hand, and aggregate economic performance on the other. They show that there is a main effect that tends to cause this relationship to be positive, and that there can be secondary effects that can either rein-force or oppose (or even overbalance) the main effect. They test the theory using the World Val-ues Survey as a source of proxies for morality. Using their preferred proxy, they find evidence that higher within-country correlation between morality and ability, holding constant the levels of morality and ability, increases per-capita income levels. Under the preferred specification, a one-standard-deviation increase in the correlation between morality and ability raises the log of per-capita income by about one-fourth of a standard deviation, equal to approximately $3,600 for the median income country in the sample. The results are robust to correcting for endogeneity and to changes in sample and specification. The results are mixed when the analysis uses alternative morality proxies, but the coefficient on the morality-ability correlation is still usually positive and statistically significant.